Low-Environmental-Input Bioproducts for Potato Culture - Mariana Calin; Nicoleta Radu; Carmen Mincea; Mihaela Doni; Roxana Zaharia (Proceedings)
Introduction: Rhizoctonia solani causes major damage to potato crops [...]